Prototype of Monitoring System for Lithium-Ion Battery Charging and Discharging on UPS Using Atmega 328p - Dedi Riswandi; Andriana Andriana; Irvan Budiawan (Journal of Mechatronics and Artificial Intelligence, 2024)
An Uninterruptible Power Supplies (UPS), is required as a backup source of power in a railroad signalling power supply system. The battery is an essential part of a UPS.  The battery functions to provide or supply electrical energy without having to be connected to electricity. Therefore, it is necessary to monitor battery conditions such as state of charge (SOC) to check battery capacity and depth of discharge (DOD) to calculate lost battery capacity. This research made a prototype of a battery monitoring system using IC ATMega328p as a microcontroller that will monitor the condition of the battery. Connecting the battery with the voltage divider circuit, the current sensor ACS712 as a current value reader at the time of charge and discharge. The results of the study showed that for the process of charging a new battery for 2 hours and 30 minutes using a 12 volt DC adapter with a current of 1.5 amperes, the current generated when the battery voltage reaches a maximum of 12,01 volts is 2,824 amperes and SOC 100%. Whereas the old battery filling took 1 hour and 30 minutes with a maximum battery voltage of 12,01 volts, 2,032 amperes, and a SOC of 100%. Whereas when the process is carried out using a battery discharge using a motor load of DC 10 volts, the time required for the discharging of the new battery is 14 hours and 30 minutes, with the current produced when the voltage of the battery reaches the minimum voltage of 8,98 volts, or 2,138 ampers, and DOD 0%.